Revisiting super-cycles in commodity prices - Fatma Pinar Erdem; Ibrahim Unalmis (Central Bank Review (CBR), 2016)
It is argued that business cycles have been moderating. However, there are a limited number of studies in the literature analyzing the cyclical behaviour of commodity prices in the last decades. This paper attempts to fill this gap by investigating the super-cycles in oil prices. In addition, interdependence between cycles in GDP and oil prices and co-movements between cycles in oil and other commodity prices are investigated. Results show that super-cycles in oil prices still exist and are not moderating. The last peak in long-term oil price was observed in 2012 and since then it has been on a downward trend.
Keywords: C22; E32; Q02; 330; Super-cycles; Commodity prices; Band-pass filters